2009
DOI: 10.3109/14992020903082088
|View full text |Cite
|
Sign up to set email alerts
|

Sentence recognition in noise: Variables in compilation and interpretation of tests

Abstract: Tests of sentence recognition in noise constitute an essential tool for the assessment of auditory abilities that are representative of everyday listening experiences. A number of recent articles have reported on the development of such tests, documenting different approaches and methods. However, both the development and interpretation of these tests require careful consideration of many variables. This article reviews and categorizes the stimulus, presentation, subject, response, and performance variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 103 publications
0
70
0
3
Order By: Relevance
“…The procedures followed in the development of the test were developed after thorough examination of existing literature on the different variables involved in the test (Theunissen et al, 2009). The development of the American English HINT (Nilsson et al, 1994) and subsequent adaptations of the HINT in other languages were particularly valuable in guiding the planning of the research.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The procedures followed in the development of the test were developed after thorough examination of existing literature on the different variables involved in the test (Theunissen et al, 2009). The development of the American English HINT (Nilsson et al, 1994) and subsequent adaptations of the HINT in other languages were particularly valuable in guiding the planning of the research.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Ana Carolina de Oliveira Sobreira (1) , Bianca Maria Capo (1) , Thássia Silva Dos Santos (2) , Daniela Gil…”
Section: Desenvolvimento De Fala E Linguagem Na Deficiência Auditiva:unclassified
“…Patients with hearing loss require that the diagnosis be made early so that a reduced impact on language development, auditory and cognitive abilities occurs. Thus, the interval between the suspected hearing loss, diagnosis and intervention should be minimized [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…The LPP had been applied with the strategy that considered as correct answer only the full recognition of a sentence (20,27) . However, this form of analysis is believed to have failed to consider important information when the individual was not able to recognize only one word in the sentence (4) . Several attempts were made before adopting this strategy, such as grouping of words or even disregard of function words.…”
Section: Development Of New Protocolmentioning
confidence: 99%
“…Among materials cited, the use of sentences in hearing evaluation has not been widespread in clinical practice yet, although there are numerous literature quotes addressing their importance (1,4) . These authors suggested wider use of sentences because sentences provide a more realistic condition compared to that of daily communication, which reinforces their importance and encourages their use in day-to-day practice.…”
Section: Introductionmentioning
confidence: 99%